HUBUNGAN ANTARA KOMUNKASI TERAPEUTIK DENGAN KECEMASAN PASIEN PRE OPERASI DI RUANG RAWAT INAP DI MAYAPADA HOSPITAL TANGERANG - Retno Andriati; Ayu Rahayu; Marsondang Situmeang; Dyna Mei Lolita Sirait; Kristina Natalya Rewo; Steven Septian Wilar (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study involved 66 respondents to examine the relationship between nurses’ therapeutic communication and anxiety levels among preoperative patients at Mayapada Hospitals Tangerang. The respondents’ characteristics showed that the dominant age group was 31–65 years, with most respondents being female. In terms of educational background, the majority were senior high school graduates, and regarding occupation, most worked as private-sector employees. The results also indicated that respondents’ assessments of nurses’ therapeutic communication were mostly in the good category, while preoperative anxiety levels were generally mild. The chi-square analysis yielded a p-value of 0.023 (< 0.05); therefore, the alternative hypothesis (Ha) was accepted, indicating a significant relationship between nurses’ therapeutic communication and preoperative patients’ anxiety levels. Based on these findings, it can be concluded that nurses’ therapeutic communication plays an important role in influencing preoperative patients’ anxiety. This study is expected to be applied more specifically to preoperative patients to determine the effect of therapeutic communication in reducing patients’ anxiety levels.